ESTIMASI PROFIT LOSS HARGA KONTRAK BERJANGKA KAKAO UNTUK KEPENTINGAN PENGAMBILAN KEPUTUSAN HEDGING - Alvina Octaviani Putri; Hadi Paramu; Tatok Endhiarto; Ariwan Joko Nusbantoro; Arnis Budi Susanto (Study Program of Management Faculty of Economics and Business University of Jember, 2023)
This study aims to examine whether hedging strategies need to be implemented or not by cocoa farmers. This study uses an estimated hedging real income analysis using the Monte Carlo simulation method to predict the selling price of cocoa on the futures exchange or the futures price and the selling price of cocoa on the physical market or spot price. The historical data examined in this study are futures price data expired in 2021 and spot price data for the period December 2015 to December 2020. The results show that 85% (425 out of 500 simulations) of the estimated real hedging income are in a profit position and 15 % (75 out of 500 simulations) the estimated real hedging income is in a loss position. Based on these results it can be concluded that transacting with futures contracts is considered to provide higher prices and income than transacting in the physical market so that cocoa farmers need to implement a hedging strategy in order to protect themselves and optimize income.